The Relationship Of Vegetable And Fruit Consumption With Nutritional Status Of Children School-Age (6-10 Years Old) At Ebf 28 De Agosto, Ebf 01 De Maio Palaban, Ebf St.Antonio Oe-Cusse, Ebf Nossa Senhora De Fatima Padiae Municipiu Regiao Administrativa Espesial Oe-Cusse Ambeno Timor Leste Year 2024 - Maria Goreti Owa; Rahaju Ningtyas; Jeni Palulun; Joao Paulo Oki; Joao Bosco Dacosta; Christina Trisnawati Setiawan (CV. Inara, 2024)
This study aims to analyse the relationship between vegetable and fruit consumption andnutritional status among school-age children in Regiao Administrativa Espesial Oe-CusseAmbeno Timor Leste, and to identify factors associated with children's nutritional status.This study used a quantitative approach with a cross-sectional design. Data were collectedthrough a questionnaire that measured the frequency of vegetable and fruit consumption,and measurement of nutritional status using anthropometric indicators. The studypopulation was school-age children in Regiao Administrativa Especial Oe-Cusse AmbenoTimor Leste with the sampling technique used was simple random sampling. Fruitconsumption patterns showed that 45.4% (79 respondents) of children rarely consumedfruit (<3 times per week). Most children were malnourished, with 69.5% (121respondents) experiencing wasting. Another factor was preference for vegetables andfruits. These two factors showed a strong and significant association (r = 0.728 forvegetables, r = 0.725 for fruits, p = 0.000), indicating that children who had a highpreference for vegetables and fruits were more likely to have better nutritional status.Child age was also found to have a significant but weak association (r = 0.278, p = 0.000)with nutritional status, suggesting that although influential, child age is not the mainfactor in determining nutritional status. Preference for vegetables and fruits had asignificant relationship with children's nutritional status. Age also has an effect, althoughit is weaker. No significant relationship was found between nutritional status and parentaleducation, meal timing, and media exposure. The implication is that there is a need toincrease vegetable and fruit consumption through nutrition education programmes inschools and communities, and the development of healthy eating habits.